Komparasi Efektivitas Strategi Pemasaran Pedagang Kaki Lima Pasar Tradisional: (Studi Kasus Pedagang Keliling Dan Pedagang Tetap) - Hamizar, Arizal (Advantage: Journal of Management and Business, 2023)
This research examines the effectiveness of marketing strategies employed by mobile and stationary street vendors in traditional markets, considering five main aspects: mobility, visual appeal, customer loyalty, product diversification, and competition. Through a qualitative approach and comprehensive analysis, this study aims to provide in-depth insights into the comparison of these two marketing strategies in the context of traditional markets. The findings reveal that mobile vendors have an advantage in high mobility, enabling them to reach various market areas, while stationary vendors emphasize the importance of a fixed location in building trust and customer loyalty. In terms of visual appeal, mobile vendors tend to be more creative and dynamic, whereas stationary vendors focus on a more permanent arrangement of stalls. Building trust and customer loyalty tends to be easier for stationary vendors due to their stable presence, while mobile vendors need to exert more effort in achieving this. Product diversification is an advantage for stationary vendors, while mobile vendors face limitations due to their high mobility. Both strategies have their respective advantages and disadvantages, and marketing success depends on adapting strategies to the changing dynamics of the market.